2014
DOI: 10.1093/nar/gku584
|View full text |Cite
|
Sign up to set email alerts
|

The DEAD-box helicase Ded1 from yeast is an mRNP cap-associated protein that shuttles between the cytoplasm and nucleus

Abstract: The DEAD-box helicase Ded1 is an essential yeast protein that is closely related to mammalian DDX3 and to other DEAD-box proteins involved in developmental and cell cycle regulation. Ded1 is considered to be a translation-initiation factor that helps the 40S ribosome scan the mRNA from the 5′ 7-methylguanosine cap to the AUG start codon. We used IgG pull-down experiments, mass spectrometry analyses, genetic experiments, sucrose gradients, in situ localizations and enzymatic assays to show that Ded1 is a cap-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(113 citation statements)
references
References 100 publications
7
105
1
Order By: Relevance
“…This suggests that protein-protein and protein-RNA associations dictate CrhR localization to the thylakoid membrane and polysome, respectively. RNA-and protein-protein-dependent association of RNA helicases has been observed in other systems (14,40,41). The ease with which CrhR was removed from the membrane fraction also indicates that protein-protein interactions and not direct membrane interactions are involved.…”
Section: Figmentioning
confidence: 75%
“…This suggests that protein-protein and protein-RNA associations dictate CrhR localization to the thylakoid membrane and polysome, respectively. RNA-and protein-protein-dependent association of RNA helicases has been observed in other systems (14,40,41). The ease with which CrhR was removed from the membrane fraction also indicates that protein-protein interactions and not direct membrane interactions are involved.…”
Section: Figmentioning
confidence: 75%
“…Despite biochemical differences between DDX3X and Ded1p, DDX3X can at least partially complement a Ded1p defect in yeast (49). This observation suggests that the biological function of the helicase in yeast tolerates variation in biochemical parameters under the conditions examined in the complementation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The binding site of DDX3 to CRM1 is a matter of debate. DDX3 has a classical N-terminal NES sequence that is conserved and required for CRM1 binding in the Saccharomyces cerevisiae homolog Ded1p48,49 and the Xenopus laevis homolog An3 31. However, Yedavalli et al observed binding between CRM1 and amino acids 260–517 of DDX3 4.…”
Section: Discussionmentioning
confidence: 99%